A return to the convertibility principle? Monetary and fiscal regimes in historical perspective. The international evidence - Michael D. Bordo; Lars Jonung (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
What is the long-run relationship between monetary and fiscal policies? This paper provides an answer by examining a large set of data covering major economies during the past 115 years. The evidence suggests the existence of a close interaction between the monetary regime, that is the behaviour of the central bank/monetary authorities, and the fiscal regime, that is the tax and spending behaviour of governments as reflected in the evolution of budget deficits and public debt. In the past, a monetary regime based on the commitment to convertibility of the domestic currency into specie, the 'convertibility principle', was the prevailing pattern in the world economy. According to this principle, the fiscal regime is subordinated to the monetary regime. The monetary regime places binding constraints on fiscal policies. The major exception to this pattern occurred during major wars and their immediate aftermath when fiscal demands determined monetary policy. Since the mid 1960s and especially after the breakdown of the Bretton Woods system in the period 1971-73, monetary policy has abandoned the 'convertibility principle' and in many countries has been geared towards domestic stabilization goals, especially that of full employment. This led to a build-up of inflationary pressures in the 1970s which has been largely rolled back since the early 1980s. In the same period bond-financed fiscal policy has been used as a stabilization policy tool, when many countries accumulated debt to income ratios sufficient to threaten monetary stability. These results suggest a prediction for the future. If fiscal balance is restored in most major economies, monetary regimes based on either an internal commitment such as the goal of price stability or low inflation or an external commitment to peg to a foreign currency will prevail.
Keywords: E50; E60; H60; N10; 330; Gold standard; convertibility; monetary regimes; Bretton Woods; Wechselkurssystem; Wechselkurspolitik; Bretton-Woods-System; Geldpolitik; Finanzpolitik; Geschichte; OECD-Staaten